Clinical correlates of reduced physical activity in idiopathic pulmonary fibrosis - Bahmer, Thomas; Kirsten, Anne-Marie; Waschki, Benjamin; Rabe, Klaus F.; Magnussen, Helgo; Kirsten, Detlef; Gramm, Marco; Hummler, Simone; Brunnemer, Eva; Kreuter, Michael; Watz, Henrik (Respiration, 2016)
Background: Little is known about the consequences of idiopathic pulmonary fibrosis (IPF) for physical activity (PA). Objectives: We aimed to investigate levels of PA in IPF and to study associations of PA with lung function, exercise capacity, symptoms, and quality of life. Methods: In stable patients with IPF we measured PA (steps per day, SPD; physical activity level, PAL; minutes of moderate activity, MMA) by accelerometry (SenseWear Armband) for 1 week. We also assessed lung function (forced vital capacity, FVC; diffusing capacity for carbon monoxide, D<smlcap>LCO</smlcap>); exercise capacity (6-minute walking distance, 6MWD); dyspnea (modified Medical Research Council, mMRC); fatigue (Multidimensional Fatigue Inventory, MFI-20), and generic (12-Item Short Form Survey, SF-12) and health-related quality of life (St. George's Respiratory Questionnaire) as further clinical variables. Results: We investigated 48 patients with IPF in two centers (mean age, 67 years; 75% male; 23% on long-term oxygen therapy; mean FVC 75%pred.; mean D<smlcap>LCO</smlcap> 43%pred.; mean 6MWD 355 ± 140 m; mean SPD 5,017 ± 3,360). On a bivariate level, all clinical variables were significantly associated with SPD (p < 0.05). The associations of mMRC, MFI-20, SF-12 (physical health), and 6MWD with SPD were independent of impaired lung function (p < 0.05). At multivariate analyses, either 6MWD (total explained variance of the model, total R2: 42%) or MFI-20 (total R2: 39%) were the strongest independent predictors of SPD. Conclusion: Fatigue and exercise capacity are strong and independent predictors of PA in patients with IPF, which suggests that both measures should be assessed when the consequences of IPF for PA in daily life are studied.